Airborne bio-particulate objects at Chittagong University Campus - Pasha, MK; Hossain, Mohammad Sohrab (Bangladesh Journal of Botany, 2012)
Survey of airborne bio-particulate objects was carried out at Chittagong University Campus during October, 2006 to September, 2007. A total of 1,451 such airborne objects were encountered consisting of plant parts and non-plant parts. Flower parts made the highest contribution, followed by dermal appendages, filamentous objects, fungal spores, plant tissues and insect appendages. Maximum concentration of airborne bio-particulate objects were observed in the month of June and minimum in November. Key words: Airborne particulate objects; Plant parts; Insect appendages; Chittagong University Campus DOI: http://dx.doi.org/10.3329/bjb.v40i2.9776 Bangladesh J. Bot. 40(2): 189-191, 2011 (December)